Tính
a) 6 17 + 3 − 17
b) 11 6 + 1 4
c) − 7 18 + 11 − 18
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =35/17-18/17-9/5+4/5
=1-1=0
b: =-7/19(3/17+8/11-1)
=7/19*18/187=126/3553
c: =26/15-11/15-17/3-6/13
=1-6/13-17/3
=7/13-17/3=-200/39
a) \(\frac{2}{3}-4.\left(\frac{1}{2}+\frac{3}{4}\right)\)
= \(\frac{2}{3}-4.\frac{5}{4}\)
= \(\frac{2}{3}-5\)
= \(-\frac{13}{3}\).
b) Câu này là 117 hay \(\frac{11}{7}\) vậy bạn?
Chúc bạn học tốt!
a,17/23 + (1 - 17/23)
= 17/23 + 6/23
= 23/23 = 1
b,17/12 + 9/7 - (2/7 + 5 /12)
= (17/12 - 5/12) + (9/7 + 2/7)
= 1+1 = 2
c, 7/13 - ( 4/7 -6/13 )
= 7/13 - 4/7+ 6/13
= (7/13 + 6/13) -4/7
= 13/13 -4/7
= 1 -4/7 = 3/7
hok tốt✍️ ✍️
a) 17/23+(1-17/23)
=17/23+1-17/23
=1
b)17/12+9/7-(2/7+5/12)
=17/12+9/7-2/7-5/12
=1+1
=2
c)
7/13-(4/7-6/13)
=7/13-4/7+6/13
=1-4/7
=3/7
a) 17/23 + (1 - 17/23)
= 17/23 + 1 - 17/23
= (17/23 - 17/23) + 1
= 0 + 1 = 1
b) 17/12 + 9/7 - (2/7 + 5/12)
= 17/12 + 9/7 - 2/7 - 5/12
= (17/12 - 5/12) + (9/7 - 2/7)
= 1 + 1 = 2
c) 7/13 - (4/7 - 6/13)
= 7/13 - 4/7 + 6/13
= (6/13 + 6/12) - 4/7
= 1 - 4/7 = 3/7
d) 7/18 + 3/16 + 11/18 + 13/16
= (7/18 + 11/18) + (3/16 + 13/16)
= 1 + 1 = 1
d) sửa 7/18 + 3/16 + 11/18 + 13/16
= (7/18 + 11/18) + (3/16 + 13/16)
= 1 + 1
= 2
\(a,=\sqrt{17}-4-\sqrt{17}-2=-6\\ b,=7\left(\sqrt{3}+\sqrt{2}\right)-7\sqrt{3}-6\sqrt{2}\\ =7\sqrt{3}+7\sqrt{2}-7\sqrt{3}-6\sqrt{2}=\sqrt{2}\\ c,=\dfrac{6\sqrt{5}+12-6\sqrt{5}+12}{3}+2\sqrt{2}-\dfrac{4\sqrt{7}}{7}\\ =8+2\sqrt{2}-\dfrac{4\sqrt{7}}{7}=\dfrac{56+14\sqrt{2}-4\sqrt{7}}{7}\\ d,=\left(\dfrac{\sqrt{2}}{4}-\dfrac{6\sqrt{2}}{4}+8\sqrt{2}\right):\dfrac{1}{8}=\dfrac{-5\sqrt{2}+32\sqrt{2}}{4}\cdot8=54\sqrt{2}\)
a; A = -1 + 3 - 5 + 7 - 9 + 11 - 13 + 15 - 17
A = (-1 + 11) + ( 3 - 13) + (-5 + 15) + (7 - 17) - 9
A = 10 - 10 + 10 - 10 - 9
A = (10 - 10) + (10 - 10) - 9
A = 0 + 0 - 9
A = -9
b; B = 1+2-3-4+5+6-7-8+9+10-11-12+13+14-15-16+17+18-19-20
B = (1+2-3-4) + (5+6-7-8)+(9+10-11-12)+(13+14-15-16)+(17+18-19-20)
B= -4+(-4)+(-4)+(-4)+(-4)
B= -4 . 5
B= -20
a) 6 17 + 3 − 17 = 6 17 + − 3 17 = 3 17
b) − 7 18 + 11 − 18 = − 7 18 + − 11 18 = − 1
c) 11 6 + 1 4 = 22 + 3 12 = 25 12